PRACTICEOPOLIS: From an Imaginary City to a Graphic Novel. Issue 1 (2nd January 2018) - Megahed, Yasser; Sharr, Adam
Abstract : This essay is about a graphic novel produced as the culmination of a creative practice research project. It dramatizes real-life exchanges from project management meetings held during a live architectural project in the United Kingdom, repositioning those exchanges in an imaginary city as high-stakes public debates. The graphic novel depicts these discussions as value conflicts in order to examine the ideologies at work among architects and other actors in the construction industry. The research represents a special creative space that challenges design research practices to create new strategies and methods for design as scholarship.